Nursing care: the fruits of advance care (Cuidado y Ocupación Humana, 2024)
Nursing care is recognized as a science, discipline, and art, resulting from the interaction between nurse and patient. With the purpose of analyzing its impact on formative practice, a qualitative- descriptive study was carried out using a narrative approach, focused on the care experience provided to a pregnant patient enrolled in the early detection program for pregnancy-related alterations. Data collection was conducted through participant observation, field notes, and the application of nursing knowledge patterns, which made it possible to document actions and reflect on the nurse–patient relationship. The results show that the implementation of anticipatory care promoted significant changes in the patient’s risk behaviors, related to physical, emotional, and spiritual dimensions, with a positive impact on maternal- fetal well-being. Furthermore, it was observed that both visible and invisible interventions strengthened the patient’s autonomy, adherence to recommendations, and psychological coping. In conclusion, the study reaffirms the relevance of a holistic and humanized approach in nursing care, highlighting that these practices not only impact the integral health of patients but also enrich the epistemological and disciplinary development of the profession.
Keywords: Nursing Care; Nurse-Patient Relations; Narration; Pregnant Women; Maternal- Fetal Well-Being